AKUNTABILITAS KEUANGAN LEMBAGA FILANTROPI ISLAM DI INDONESIA - Nur Fitriyah; Herlina Pusparini; Nurabiah Nurabiah (Jurusan Akuntansi Fakultas Ekonomi Dan Bisnis Universitas Mataram, 2021)
Islamic Philanthropic Institutions must report the results of managing zakat, infaq, and alms to gain the trust of the community so that the potential for zakat, infaq, and alms collected is much greater because of the community's trust in these institutions. Therefore this study aims to determine the extent of the level of accountability in the financial transparency of the Islamic Philanthropic Institution in Indonesia as seen based on website data. This type of research is a descriptive study with a quantitative approach. The population in this study were 24 National Islamic Philanthropic Institutions that already have a Registered Certificate (SKT). Determination of the number of samples using the census method. The results of this study state that in terms of accessibility, the national Islamic philanthropy website is very accountable, meaning that the majority of Islamic Philanthropy has a website so that people can access information on Islamic Philanthropy financial statements and in terms of availability of financial reports, there are national Islamic philanthropic websites that are sufficiently accountable, are the statement of financial position and statement of changes in funds and some are less accountable, are statement of changes in managed assets and cash flow statement and there are those that are very less accountable, is notes to financial statements.